Association of Age, Gender, and Occupation With Kellgren-Lawrance Severity in Knee Osteoarthritis Patients at Pandega Pangandaran General Hospital - Himawan Widyatmiko; Rosyad Nur Khadafi (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2026)
A person's quality of life can be greatly diminished by osteoarthritis (OA), a degenerative joint disease that gradually impacts every part of the joint. It predominantly affects weight-bearing joints, particularly the hip and knee. The prevalence of disability attributable to OA rose by 114% between 1990 and 2019. Age, female gender, and physical activity are among the risk factors for OA. This study aims aimed to evaluate the association between age, gender, and occupation with Kellgren-Lawrance Severity in Knee Osteoarthritis Patients at Pandega Pangandaran General Hospital. A descriptive-analytical strategy was utilized inside a cross-sectional method in this study. The study data consisted of secondary data from knee OA patients above 40 years old registered in the medical records of Pandega Pangandaran General Hospital from January 2022 to December 2024 who had undergone radiographic examination. Data were collected through total sampling and subsequently analyzed using SPSS version 27. Correlation tests were selected to assess the association between demographic variables and ordinal Kellgren–Lawrence severity grades. Potential confounding variables, including body mass index, history of trauma, comorbidities, and physical activity level, were not controlled due to limitations of secondary data. There was a statistically significant association between age and knee OA severity (p0.001, r=0.335), indicating a weak positive correlation, and between occupation and knee OA severity (p=0.002, r=0.279), also indicating a weak positive correlation. Gender was significantly associated with knee OA severity (p=0.043, r = 0.217), also indicating a weak positive correlation. Multivariate analysis showed that occupation remained the strongest independent factor associated with severe knee OA (p=0.015; adjusted OR 4.364; 95% CI 1.330–14.320), followed by age (p=0.003; adjusted OR 3.958; 95% CI 1.583–9.897). Gender was not independently associated with OA severity after adjustment (p=0.295). In conclusion, age, gender, and occupation were significantly associated with the severity of knee OA; however, the observed correlation strengths were weak.